Penggunaan Error Correction Mechanism dalam Analisis Pengaruh Investasi Langsung Luar Negeri Terhadap Pertumbuhan Ekonomi Indonesia - fitri kartiasih; satria june adwendi (Program Studi Statistika Unisba, 2016)
A developing country like Indonesia would require funds to increase their economic performance. The contribution of savings are not enough to finance national development. It is necessary to find other financial resources which is foreign direct investment. Error Correction Meccanism (ECM) is used to analyse the influence of foreign direct investment and other interconnected sectors in open economy like domestic credit, government spending, and inflation to economic growth. The result shows that domestic credit, government spending, and inflation increase, but government spending and foreign direct investment tends to be fluctuating from 2000-2014. The research results also showed that economic growth in the long term is influenced by domestic credit and inflation, while in the short term are influenced by foreign direct investment and domestic credit.